Investigation of Boron addition and compaction pressure on the compactibility, densification and microhardness of 316L Stainless Steel - Ali, S. (Institute of Physics Publishing, 2018)
Powder Metallurgy (P/M) is one of the continually evolving technologies used for producing metal materials of various sizes and shapes. However, some P/M materials have limited use in engineering for their performance deficiency including fully dense components. AISI 316L Stainless Steel (SS) is one of the promising materials used in P/M that combines outstanding corrosion resistance, strength and ductility for numerous applications. It is important to analyze the material composition along with the processing conditions that lead to a superior behaviour of the parts manufactured with P/M technique. This research investigates the effect of Boron addition on the compactibility, densification, sintering characteristics and microhardness of 316L SS parts produced with P/M. In this study, 0.25 Boron was added to the 316L Stainless Steel matrix to study the increase in densification of the 316L SS samples. The samples were made at different compaction pressures ranging from 100 MPa to 600 MPa and sintered in Nitrogen atmosphere at a temperature of 1200Â°C. The effect of compaction pressure and sintering temperature and atmosphere on the density and microhardness was evaluated. The microstructure of the samples was examined by optical microscope and microhardness was found using Vickers hardness machine. Results of the study showed that sintered samples with Boron addition exhibited high densification with increase in microhardness as compared to pure 316L SS sintered samples. Â© Published under licence by IOP Publishing Ltd.